Neurocognitive processing in dyslexic children: an event related potential (ERP) study - Ali, Siti Atiyah (2021)
Dyslexic children have been reported to have an attentional neurocognitive deficit in processing sensory stimulations. Due to that, this study was aimed to investigate the neurocognitive attentional processing of dyslexic children comparing to the healthy control children in different auditory and visual stimuli paradigms by using the Event-Related Potential (ERP) technique. A total of 24 primary school-aged children were recruited for the dyslexic (n=12) and control (n=12) groups. 128-EEG child sensor net was used for the ERP study. There were four different stimulus paradigms were used in this study which was; auditory oddball, paired audio-visual, visual image congruency, and pseudo words/true words. For the first two paradigms, the MMN and P300 ERP components were analysed for the auditory and shifted attention. Alternatively, the N200 and P300 were analysed for visual attentional processing in the other two paradigms. The values of difference wave between target and standard stimuli were measured in both groups in the 10-20 system at 19 electrodes. Then, the Mann Whitney U test statistical analysis was used to analyse the mean difference amplitudes and latencies for each ERP component between dyslexic and control groups. Besides, source localizations of MMN, N200, and P300 ERP components were done for all paradigms using the Standardized Low-Resolution Brain Electromagnetic Tomography (sLORETA) method in Net-station software. For the result findings, during the auditory oddball paradigm, MMN amplitudes were significantly higher (4 sites) and prolonged latency (1 site) in dyslexics compared with the control. P300 amplitudes were significantly larger at 2 sites, whilst the P300 latencies were significantly shorter and prolonged (in 2 sites each) in the dyslexic children than control children. The source activities of both ERP components in dyslexics were seen lateralized in the right hemisphere with MMN (BA18) and P300 (BA9). In audio-visual paired stimuli, there were significantly shorter P300 latencies (2 sites) among dyslexics which seen both ERP components activated in the left hemisphere during MMN (BA3) and P300 (BA19). In visual image congruency stimuli, significant prolongation of N200 latencies (2 sites) and significantly shorter P300 latency (1 site) among dyslexics than the controls. The source activities were seen in the left occipital lobe of BA 18 (in N200) and BA19 (in P300) areas in dyslexics. For the pseudo word/true words stimuli paradigm, significantly larger amplitudes of N200 (1 site) and P300 (2 sites) with shorter latencies of both components (1 site) were evoked in dyslexics. However, the source activities of N200 and P300 components in dyslexics were located in the BA39 and BA19 areas, accordingly. In conclusion, the ERP findings showed that there were a betterment and enhancement in attentional cognitive function in all auditory and visual task paradigms among dyslexics than the controls, suggested on different neuronal mechanism processing among dyslexics in overcoming the undetermined deficit that was also supported with shifted neural source activities.